2020
DOI: 10.1007/s00170-020-05397-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance evaluation of TiO2, and MWCNTs nano-lubricant effects on surface roughness of AA8112 alloy during end-milling machining for sustainable manufacturing process

Abstract: Aluminium 8112 alloy has become a leading material in the aluminium family and currently used in the aerospace and automobile industries due to its excellent chemical and mechanical properties. However, during machining of aluminium alloy, one of the challenges faced by the manufacturing industry is the material adhesion, which increases the rate of chips discontinuity at the machining region and leads to a high surface roughness of the workpiece. The focus of this research is to proffer solutions to this mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The elevated FR normally produce vibrations between the composite material and cutting tool. This causes an increase in intensity of surface roughness for the duration of cutting operation [29]. Likewise, expanding the FR results a rise in the machined sign owing to more contact area creation that leads to additional forces and consequently Ra parameter emerges considerably [30].…”
Section: Analysis Of Variance (Anova)mentioning
confidence: 99%
“…The elevated FR normally produce vibrations between the composite material and cutting tool. This causes an increase in intensity of surface roughness for the duration of cutting operation [29]. Likewise, expanding the FR results a rise in the machined sign owing to more contact area creation that leads to additional forces and consequently Ra parameter emerges considerably [30].…”
Section: Analysis Of Variance (Anova)mentioning
confidence: 99%
“…The time taken to turn the composite material when using mineral oil compared to when using MWCNT nano lubricant was reduced. This is due to the flow rate of the two lubricants employed for the experiment; when the MWCNT nanoparticles were added to the mineral oil, it increased the tribological properties and the viscosity of the fluid flow [25]. This increase in viscosity affects the cut time by increasing it compared with the mineral oil.…”
Section: Temperature Variation Under Mineral Oil Lubrication and Mwcn...mentioning
confidence: 99%
“…They reported that the TiO 2 nano-lubricant resulted in lower surface roughness compared to the copra oil and MWCNT nano-lubricant. 62…”
Section: Surface Roughness Of Precision-machined Advanced Engineering Materialsmentioning
confidence: 99%
“…They reported that the TiO 2 nano-lubricant resulted in lower surface roughness compared to the copra oil and MWCNT nanolubricant. 62 The demands for cleaner manufacturing motivate manufacturers to benefit from low carbon footprint on the environment and high machinability. Because of the outstanding heat transfer ability, nano-lubricants have great acceptability for eco-friendly and sustainable machining of superalloys.…”
Section: Surface Roughness Of Precision-machined Advanced Engineering Materialsmentioning
confidence: 99%